Accuracy of Duplex Ultrasonography in Estimation of Severity of Peripheral Vascular Disease - Franz, Randall W.; Jump, Mark A.; Spalding, M. Chance; Jenkins, James J., II (International Journal of Angiology, 2013)
Duplex ultrasonography (DUS) is a safe, noninvasive method for imaging vasculature when compared with conventional angiography. Our goal is to assess the accuracy of DUS compared with angiography of the lower extremities. We reviewed a total of 373 lesions in 278 patients from July 2005 through June 2010. Patients underwent DUS followed by angiography within 30 days. Peak systolic velocities (PSV) were stratified into one of four categories and compared with the angiographic findings. Seventy-five chronic total occlusions were found. Of the remaining 298 lesions, a significant relationship was found between PSV and degree of angiographic stenosis (p < 0.001). DUS was found to demonstrate a sensitivity of 79.7%, specificity of 79.2%, positive predictive value of 88.2%, and negative predictive value of 66.7% for lesions ≥ 70%. The 66.7% of the false-negative lesions with the lowest velocities were below the knee joint. DUS of the lower extremities is accurate in determining the degree of stenosis ranging from mild-to-severe disease. Some limitation may exist in estimating the degree of stenosis below the knee.
Keywords: duplex ultrasonography; contrast angiography; peripheral arterial disease